Recent trends in caries diagnosis - Priyatama Meshram; Vikas Meshram; Abhishek Soni; Praveen Sundarkar; Aparna Thombre; Vivek Thombre; Savita Ghom (Wolters Kluwer Medknow Publications, 2011)
To create opportunity for a preventive approach to the management of caries, it is important to keep abreast of developments in diagnostic systems. It is apparent that conventional methods for the detection of dental canes do not fulfill the criteria for an ideal canes detection method. These methods rely on subjective interpretation and are insensitive to early canes detection. To overcome these shortcomings, researchers are developing advanced techniques. These not only detect mineral loss but also quantify it.